OPTIMASI DOSIS PUPUK NPK DAN ASAM HUMAT DALAM MEMPERBAIKI KUALITAS TANAH BEKAS TAMBANG BATUBARA DAN PERTUMBUHAN SENGON SOLOMON - Tampubolon, Gindo; Lagowa, Muhammad Ikrar; Simarmata, Jhoy Michael; Sitanggang, Boy Julius (Jurnal Teknologi Mineral dan Batubara, 2023)
Solomon Sengon (Paraserianthes mollucana (Miq.) Barneby & J.W. Grimes) is a plant species in land reclamation activities for former coal mines. This is because Solomon sengon has advantages including: very fast growth, adaptive to extreme environments, and quite high economic and ecological values. Former coal mining soils are generally degraded and have low organic matter content, essential nutrient availability, CEC, and base saturation. These conditions do not support optimal plant growth. The aim of this study was to examine the effect of NPK plus humic acid fertilizer on several soil chemical properties and the growth of the Solomon sengon plant. This research was carried out in the coal mining concession area in Amplelu Mudo Village, Tembesi District, Batang Hari Regency, Jambi Province. The study used a randomized block design (RBD) with doses of NPK plus humic acid fertilizer in 9 levels and repeated 3 times, so there were 27 plots or experimental units. The observed variables were: pH, Al-dd, available-P, K-dd, height increase, diameter increase and root dry weight. The results showed that the application of NPK fertilizer 100 g plus humic acid 20 g/plant hole (P5) was the best treatment in improving soil K-dd with an increase in plant height of 110.83 cm, diameter of 28.65 mm and BKA of 10.63 g , there was an increase in the height of the Solomon sengon plant by 101.21%, diameter by 65.13% and BKA by 75.12% compared to the administration of 50 g NPK plus 10 g humic acid (P1). Increasing the dose of NPK and humic acid from 50 g of NPK plus 10 g of humic acid to 100 g of NPK and 20 g of humic acid has the potential to significantly increase the growth of the Solomon sengon plant.